Handbook of Vascular Motion - Cheng, Christopher; Cheng, Christopher (Elsevier Science, 2019)
Handbook of Vascular Motion provides a comprehensive review of the strategies and methods to quantify vascular motion and deformations relevant for cardiovascular device design and mechanical durability evaluation. It also explains the current state of knowledge of vascular beds that are particularly important for the medical device industry. Finally, it explores the application of vascular motion to computational simulations, benchtop testing and fatigue analysis, as well as further implications on clinical outcomes, product development and business.Describes methods to quantify vascular motion and deformations including choosing what data to collect, relevant medical imaging, image processing, geometric modeling, and deformation quantification techniquesIncludes deformations for vascular beds of particular importance in medical devices including the coronary arteries and heart, arteries of the head and neck, thoracic aorta and arch branches, abdominal aorta and visceral branches, lower extremity arteries, inferior vena cava, and lower extremity veinsExplains how to convert raw deformations into boundary conditions suitable for durability evaluation, provides examples of using this information for computational simulations, benchtop testing, and fatigue analysis, and illustrates examples of how vascular motion affect clinical outcomes, product development, and business